New perspectives on Eastern Baltic cod movement patterns from historical and contemporary tagging data - Mion, M; Griffiths, CA; Bartolino, V; Haase, S; Hilvarsson, A; Hüssy, K; Krüger-Johnsen, M; Krumme, U; Lundgreen, RBC; Lövgren, J; McQueen, K; Plikshs, M; et al.
2022